2021
DOI: 10.1111/tri.13787
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between proteinuria and allograft survival in patients with transplant glomerulopathy: a retrospective single‐center cohort study

Abstract: Summary Proteinuria and transplant glomerulopathy (TG) are common in kidney transplantation. To date, there is limited knowledge regarding proteinuria in different types of TG and its relationship to allograft survival. A retrospective cohort analysis of TG patients from indication biopsies was performed to investigate the relationship of proteinuria, histology, and graft survival. One hundred and seven (57.5%) out of 186 TG patients lost their grafts with a median survival of 14 [95% confidence interval (CI) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Regarding the etiology of mm, our data showed that 39% of mm-positive lesions had ABMR ( Figure 3 ). Similarly, a recent study stated that transplant glomerulopathy affects approximately half of the patients with chronic active ABMR, and the Banff mm score reflects poor graft survival [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the etiology of mm, our data showed that 39% of mm-positive lesions had ABMR ( Figure 3 ). Similarly, a recent study stated that transplant glomerulopathy affects approximately half of the patients with chronic active ABMR, and the Banff mm score reflects poor graft survival [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four of five mm-positive patients with transplant glomerulopathy and proteinuria experienced graft loss ( Figure 6 ). A recent study of transplant glomerulopathy showed that the level of proteinuria and the presence of mm ≥ 1 affect the graft survival [ 15 ]. Electron microscopy reveals endothelial injury in glomeruli in ABMR leading to transplant glomerulopathy [ 19 ], and we also recently reported that the electron microscopic findings of glomerular endothelial injury are detected in patients with low-level proteinuria with ABMR [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individualized treatment strategies and close follow-up monitoring should be adopted for patients with FSGS to improve allograft outcomes. Previous studies [14, 28, 29] have indicated that proteinuria and impaired renal graft function at biopsy were independent risk factors for allograft loss in TG. Relative histopathological risk factors including interstitial fibrosis [21, 30], chronic score [15, 28], cg [22], and glomerular C3 deposition [15] have also been reported but are not seen in our study, probably due to the limited sample size and to the differences in follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective analysis of TG in 954 kidney transplant recipients (3744 biopsies) found that TG occurred in >75% of the patients in the absence of HLA-DSA, independent of HLA molecular mismatches; it represented a different phenotype that had lower levels of concomitant inflammation and graft loss compared with HLA-DSA+ TG ( 56 ). An additional recent retrospective study found that proteinuria, C4d presence, and mesangial matrix expansion were important for outcome, while other histological markers (e.g., Banff Lesion Score cg) were not ( 57 ).…”
Section: Banff Classification: Amr Subcategories As Endpointsmentioning
confidence: 99%